2015
DOI: 10.1016/j.apmr.2014.09.019
|View full text |Cite
|
Sign up to set email alerts
|

It Takes Two: Noninvasive Brain Stimulation Combined With Neurorehabilitation

Abstract: The goal of post-acute neurorehabilitation is to maximize patients' function, ideally by using surviving brain and central nervous system tissue when possible. Yet the structures incorporated into neurorehabilitative approaches often differ from this target, which may explain why efficacy of conventional clinical treatments targeting neurological impairments varies widely. Non-invasive brain stimulation such as with Transcranial Magnetic Stimulation (TMS) and transcranial direct current stimulation (tDCS) offe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 48 publications
0
32
0
Order By: Relevance
“…Additionally, tDCS and TMS are proven to be well-tolerated, inexpensive, and safe with few adverse effects. Moreover, tDCS, a portable device with simplicity of its mode of action, offers the possibility of use as a home-based treatment (Page et al, 2015 ). Last but not the least, EA is minimally invasive and shares safe, efficacious, and inexpensive similarities with TMS and tDCS.…”
Section: Discussion and Future Directionmentioning
confidence: 99%
“…Additionally, tDCS and TMS are proven to be well-tolerated, inexpensive, and safe with few adverse effects. Moreover, tDCS, a portable device with simplicity of its mode of action, offers the possibility of use as a home-based treatment (Page et al, 2015 ). Last but not the least, EA is minimally invasive and shares safe, efficacious, and inexpensive similarities with TMS and tDCS.…”
Section: Discussion and Future Directionmentioning
confidence: 99%
“…49 Very recently, non-invasive brain stimulation also has been added to the array of stimulation-based tools that might augment neurorehabilitation practices. 50 Generally speaking, these devices are designed to deliver predictable, linear patterns of stimulation for the purpose of facilitating movement (e.g., muscle activation, kinematics, etc). In the future, such devices potentially could be designed to deliver stimulation containing multifractal features, with the specific intent of enhancing and diversifying the adaptive capacity of a patient’s movement system.…”
Section: Future Directionsmentioning
confidence: 99%
“…stem cell induction), remyelination (oligodendrocyte function), and spinal plasticity modulation (reduced inhibition). 13 We may hypothesize that our rTMS paradigm could have strengthened the RAGT's effects thanks to either direct cortico-spinal or trans-synaptic spinal effects. 14 Indeed, it has been shown that rTMS could decrease intracortical inhibition phenomena and shape I-waves, allowing the recruitment of the spared corticospinal tract fibers, and thus improving the motor functions.…”
Section: 11mentioning
confidence: 99%